PENGARUH DESENTRALISASI DAN KOMITMEN ORGANISASIONAL TERHADAP HUBUNGAN ANTARA PENGANGGARAN PARTISIPATIF DAN KINERJA MANAJERIAL - Ikhsan Budi Rihardjo (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2009)
The purposes of this research are to test empirically and analyze whether or not there is relationship between participative budgeting and managerial performance, as well as to test empirically and analyze whether decentralization and organizational commitment as moderating variables influence the relationship between participative budgeting and managerial performance in local government. The samples of this research are taken from local government organization population, that is the partner of local apparatus working unit (Satuan Kerja Perangkat Daerah/SKPD) until two level under SKPD manager. From 420 shared questionnaires, there are founded 147 respondents whos return their answers, and only 98 questionnaires, which fulfill the requirement to be computed and involved in final analysis.Hypotheses testing technique that is used to test the relationship between participative budgeting and managerial performance is simple regression. And to test influential interaction of two contingency factor (decentralization and organizational commitment), Moderated Regression Analysis (MRA) is used. The empirical result using simple regression show that participative budgeting influences the managerial performance in local government organization. While empirical result using moderated regression analysis shows that the Interaction between participative budgeting and decentralization structure affects managerial performance significantly. Interaction between participative budgeting and organizational commitment does not affect managerial performance of local government organization significantly.